The seer and the city : religion, politics, and colonial ideology in ancient Greece - Foster, Margaret, 1977- (Joan Palevsky imprint in classical literature., 2017)
"Seers featured prominently in ancient Greek culture, but they rarely appear in colonial discourse from the archaic and classical periods. Margaret Foster exposes the ideological motivations behind this discrepancy and reveals how colonial discourse's privileging of the city's founder and his dependence on Delphi, the colonial oracle par excellence, entails a corresponding suppression of the seer. Foster explains why the seer's authority conflicts with that of the founder and investigates a sequence of literary works from a range of genres that showcase this dynamic. The first study to analyze the seer and the Delphi-sanctioned founder relationally, this volume illuminates the contests between religious and political powers in archaic and classical Greece."--Provided by publisher.